Efektifitas Edukasi Audio Visual Terhadap Kecemasan Pasien sebelum Tindakan Gastroscopy: Studi Systematic Review dan Meta-Analysis - Bayu Aji Sismanto; Nurhayati Khaier; Yeni Purnamasari; Yahya (Jurnal Keperawatan Nusantara, 2025)
Background: Gastroscopy is a diagnostic procedure to view organs visually using a lat connected to a monitor, the organs viewed are the esophagus, gastric and duodenum. Anxiety in patients before gastroscopy occurs due to fear by imagining. Education is carried out as a pre-action procedure to explain the actions that will be performed. Objective: We conducted a systematic review and meta-analysis to investigate the effect of audio-visual education on patient anxiety before gastroscopy. Results: Four articles were included in this study, audiovisual education significantly reduced patients' anxiety before gastroscopy using Visual analogue scale (VAS); one study used Anxiety and Stress Scale-42 (DASS-42) and one study used State Trait Anxiety Inventory (STAI). Based on a randomized control trial, it was found that education was effective in reducing anxiety by -4.38 (95% CI: -14.3796 to 5.6198), indicating insignificant results. And obtained I² value of 99.9607%, Q value of 1017.3516, and P value <0.0001 which means that heterogeneity is high. The range of results obtained was -26.7290 to 17.9692 with three negative results and one possible positive result (Khan, et.all, 2023) with a residual value of (± 2.4977) In the regression test results showed asymmetry in the flores plot (p < 0.0001) but did not show a rank correlation test (p = 0.7500). Clinical Implications: Audio-visual education is a potentially promising method for controlling anxiety in patients undergoing gastroscopy; however, its effect in controlling anxiety is controversial.